Early imaging predictors of longer term multiple sclerosis risk and severity in acute optic neuritis. Issue 3 (July 2019) - Gajamange, Sanuji; Stankovich, Jim; Egan, Gary; Kilpatrick, Trevor; Butzkueven, Helmut; Fielding, Joanne; van der Walt, Anneke; Kolbe, Scott
Background: Biomarkers are urgently required for predicting the likely progression of multiple sclerosis (MS) at the earliest stages of the disease to aid in personalised therapy. Objective: We aimed to examine early brain volumetric and microstructural changes and retinal nerve fibre layer thinning as predictors of longer term MS severity in patients with clinically isolated syndromes (CIS). Methods: Lesion metrics, brain and regional atrophy, diffusion fractional anisotropy and retinal nerve fibre layer thickness were prospectively assessed in 36 patients with CIS over the first 12 months after presentation and compared with clinical outcomes at longer term follow-up [median (IQR) = 8.5 (7.8–8.9) years]. Results: In total, 25 (69%) patients converted to MS and had greater baseline lesion volume ( p  = 0.008) and number ( p  = 0.03)than CIS patients. Over the initial 12 months, new lesions ( p  = 0.0001), retinal nerve fibre layer thinning ( p  = 0.04) and ventricular enlargement ( p  = 0.03) were greater in MS than CIS patients. In MS patients, final Expanded Disability Status Scale score correlated with retinal nerve fibre layer thinning over the first 12 months (ρ = −0.67, p  = 0.001). Conclusions: Additional to lesion metrics, early measurements of fractional anisotropy and retinal nerve fibre layer thinning are informative about longer term clinical outcomes in CIS.